Students’ Difficulties and The Teacher’s Response: Emerging Solution to Solve Alqur’an Reading Problems of young learners - jaenullah jaenullah; Mispani Mispani; Rahayu hidayah; Ridwan As'ari (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
This study aims to determine and measure the efforts and responses of Islamic Religious Education (PAI) teachers in overcoming elementary school students' or young learners’ difficulties in reading the Qur'an and its influence. In its implementation, researchers used the An-Nahdliyah method in responding to the difficulties of students in reading the Qur'an. This research uses a quantitative approach with an experimental design. The results of this study indicate that Islamic Religious Education (PAI) teachers have a good effort and response. This is evident from the results of Chi square calculation of 20.27 and a significance level of 5%. In addition, the results of the analysis of the correlation coefficient or KK = 0.66 lies at intervals of 0.600 to 0.800. Thus the influence between the role of Islamic Religious Education (PAI) teachers in overcoming the difficulty of reading the Qur'an elementary school students or young learners can be categorized quite well